KONSEP MASLAHAT MENURUT IMAM MĀLIK - Ikhsan, Muhammad; Iskandar, Azwar (UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to analyze: imam Mālik's position in the Islamic jurisprudence map; the concept of maslahat in the perspective of Imam Mālik; and the influence of Imam Mālik's maslahat view in the Islamic world. This research is qualitative descriptive research, using library research and analyzed with historical and sociological approaches. The results of the study found that: first, Imam Mālik bin Anas was one of the imams of the four sects (mazhab) who exerted great influence in Muslims with his ability as a mujtahid and had an independent methodology in conducting the ijtihad; second, one of the most important foundations of Imam Mālik's ijtihad is maslahat. In this case, he actually had similarities with the other ultimate scholars of the four sects. Māliki sect, namely that maslahat -especially maslahat mursalah- is a stand-alone proposition; third, Imam Mālik's assertiveness in positioning maslahat as one of the independent evidences in his ijtihad methodology has stimulated the fiqh researchers to study further explore this so that imam Mālik's fiqh sect can survive to this day and successfully produce phenomenal scientific works that affirm the existence of maslahat as one of the footholds of Islamic law.